2020
DOI: 10.1007/s12020-020-02480-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of differences in bone microarchitecture in adult- versus juvenile-onset type 1 diabetes Asian males versus non-diabetes males: an observational cross-sectional pilot study

Abstract: Purpose Evidence about bone microarchitecture in Asian type 1 diabetes (T1D) patients is lacking. We assessed the bone microarchitecture in T1D patients versus controls and compare the differences between juvenile-onset and adult-onset T1D patients. Methods This cross-sectional study recruited 32 Asian males with T1D and 32 age-, sex-, and body mass index (BMI)-matched controls. Dual-energy X-ray absorptiometry (DXA) and high-resolution periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…Previous studies have found low bone turnover especially reduced bone formation in the T1D context ( 26 ); however, the bone resorption can be enhanced, inhibited, or unaltered, which might be attributed to the timing of onset of T1D, the duration of diabetes, and the disease-associated inflammatory environment ( 27 ). In our study, STZ-induced T1D mice showed significantly elevated blood glucose for an enough duration (at least 8 weeks), resulting in decreased BMD and compromised microarchitectures, which was consistent with previous clinical and animal studies ( 3 , 14 , 25 , 28 ), indicating our successful establishment of the disease model. Thus, the STZ-induced T1D model could be a convenient and reliable model for studying T1D-related bone loss.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have found low bone turnover especially reduced bone formation in the T1D context ( 26 ); however, the bone resorption can be enhanced, inhibited, or unaltered, which might be attributed to the timing of onset of T1D, the duration of diabetes, and the disease-associated inflammatory environment ( 27 ). In our study, STZ-induced T1D mice showed significantly elevated blood glucose for an enough duration (at least 8 weeks), resulting in decreased BMD and compromised microarchitectures, which was consistent with previous clinical and animal studies ( 3 , 14 , 25 , 28 ), indicating our successful establishment of the disease model. Thus, the STZ-induced T1D model could be a convenient and reliable model for studying T1D-related bone loss.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with bone histomorphology or local gene expression, serum turnover markers may be less sensitive. In our study and other studies, serum CTX or P1NP in T1D patients was within the normal range or similar to the control groups, while micro-CT found significant compromised microarchitectures (3,25). Previous studies have found low bone turnover especially reduced bone formation in the T1D context (26); however, the bone resorption can be enhanced, inhibited, or unaltered, which might be attributed to the timing of onset of T1D, the duration of diabetes, and the disease-associated inflammatory environment (27).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, subjects with long-standing T1D manifested impairments in cortical vBMD, cortical bone thickness, and estimated strength and stiffness at the ultradistal tibia, that were reported to be determined by diabetic neuropathy [27 && ]. These findings disagree with previous studies assessing bone microstructure with HR-pQCT where impairments in trabecular bone were reported in subjects with T1D compared to controls [28][29][30][31].…”
Section: High-resolution Peripheral Quantitative Computed Tomographycontrasting
confidence: 99%
“…Hence, BMD cannot solely explain the increased fracture burden in T1D. Newer studies have suggested that people with T1D may also have an increased bone fragility from decreased bone quality, which partly explains the increased risk of fractures [19][20][21].…”
Section: Tablementioning
confidence: 99%